2017
DOI: 10.1093/mnras/stx3132
|View full text |Cite
|
Sign up to set email alerts
|

CONSERT constrains the internal structure of 67P at a few metres size scale

Abstract: The internal properties of cometary nuclei are the best clues to the size distribution and properties of the early planetesimals that formed the planets during the early Solar system nebula processes. The CONSERT radar was designed to probe the interior of comet 67P/Churyumov-Gerasimenko with a wavelength of about 3 m. It was successfully operated during the First Science Sequence of the Rosetta mission when the CONSERT's wave propagated through part of the nucleus' small lobe. The shape of the received signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 75 publications
(62 reference statements)
3
18
0
Order By: Relevance
“…As a second step, the absence of scattering was quantified in terms of maximum size of the possible scatterers and of maximum deviation with respect to the average bulk permittivity, in order to assess the maximum size and contrast of the possible heterogeneities for which no signal spreading can be observed. This study was carried out using numerical simulations of electromagnetic wave propagation (Ciarletti et al 2017). The results are listed below.…”
Section: Compositional Homogeneity Of 67p As Seen By Consertmentioning
confidence: 99%
See 1 more Smart Citation
“…As a second step, the absence of scattering was quantified in terms of maximum size of the possible scatterers and of maximum deviation with respect to the average bulk permittivity, in order to assess the maximum size and contrast of the possible heterogeneities for which no signal spreading can be observed. This study was carried out using numerical simulations of electromagnetic wave propagation (Ciarletti et al 2017). The results are listed below.…”
Section: Compositional Homogeneity Of 67p As Seen By Consertmentioning
confidence: 99%
“…After the landing of Philae, the Comet Nucleus Sounding Experiment by Radiowave Transmission (CONSERT) on board Rosetta probed the nucleus of 67P/Churyumov-Gerasimenko (67P) and observed no heterogeneities at metric scale within the fathomed part of the small lobe of the comet (Kofman et al 2015). The observed homogeneity has later been quantified in term of maximum permittivity contrast versus typical size (Ciarletti et al 2017). The aim of this paper is to interpret this limit in sensitivity of the measurements in terms of composition, and to provide constraints on the maximum variability in composition, porosity, and local dust-to-ice mass ratio (D/I).…”
Section: Introductionmentioning
confidence: 99%
“…While the internal structure of the comet beneath the visible surface remains largely unknown (see below), some measurements have increased our knowledge. Brouet et al (2016) showed that CONSERT and SESAME-PP data indicate that the porosity increases with the increasing depth in the small lobe of the nucleus (see also Ciarletti et al 2017).…”
Section: Some Knowledge Of Depth Structurementioning
confidence: 93%
“…Consequently, only part of the nucleus's small lobe has been sounded and characterised. On the detected signals, only the propagation delays and the shape of the received pulses have been analysed and provided an average value for the real part of the permittivity and some hints about the spatial variations (Brouet et al 2016; and the limited heterogeneity inside the sounded area (Ciarletti et al 2017). The interpretation of the received amplitudes would have brought further constraints on the nucleus composition that have already been obtained ) but would require a better knowledge of the Philae's antenna radiation pattern in the actual local environment.…”
Section: Deep Interiormentioning
confidence: 99%
“…λ/2 at the surface of the body. Under this constraint, when a full tomography of the body [32,33] is not feasible with a priori information [34], then statistical tomography allows to characterize heterogeneity scales [35] and to retrieve composition information (for CONSERT see also [36] and [37]). However, it is likely that a combination of higher data volume by utilization of additional passes, allocation of more ground station time, or mission extension, together with any better than worst-case power availability on the lander platform can result in a much better tomographic coverage.…”
Section: Accepted Manuscriptmentioning
confidence: 99%